Practice of Triple Helix (TH) Model in Malaysian Research Universities (RU) - Afzal, Munshi Naser Ibne; Dutta, Susmita; Mansur, Kasim Bin HJ. MD.; Lawrey, Roger (School of Business and Management Institut Teknologi Bandung, 2017)
Abstract. Innovation is one of the key elements of countriesâ€™ competitiveness. In the face of continuous world economic changes, the Triple Helix Model (University-Industry-Government) relationship allows many countries to improve and accelerate their innovation processes. In developing countries, which are in transition towards innovation-based economies, such as Malaysia, Triple Helix (TH) can serve as a tool to speed up this transition. Â This paper explores the implementation of Triple Helix to discover the extent of collaboration between companies and universities both on a global scale and particularly in Malaysia. The study uses a quantitative methodology based on an integrative analysis of literature, secondary data and results of a survey, conducted among four Malaysian research based universities. The research finds that the average performance of Malaysian research based public universities in the Triple Helix system is generally good. For individual universities this study finds that the National University of Malaysia (UKM) has performed above average, while University of Malaya (UM) shows below average performance among major research universities in Malaysia. The findings of this research highlight the need to solve the identified problems in parallel with implementation of the open innovation concept in university-industry collaborations. Â Keywords: Triple Helix, Research University (RU), Technology Commercialisation, Innovation, Malaysia